English Vocabulary Learning Strategies Used by The Eleventh-Grade Students of MAN 1 BIMA - Nur Aisyah; Lalu Thohir; Ahmad Zamzam; Boniesta Zulandha Melani (Jurnal Ilmiah Profesi Pendidikan, 2025)
This study used a descriptive qualitative method to describe the Vocabulary Learning Strategies (VLS) and discover the most dominant strategies used by the eleventh-grade students of MAN 1 Bima. The subjects were 15 male and 15 female students. The data were collected using a questionnaire of 40 items selected from Schmitt’s (1997) Vocabulary Learning Strategies Questionnaire (VLSQ). Interviews were also conducted to obtain more information from the students. The data was calculated using the Likert scale formula in the MS Excel software package. The result shows that male and female students employed more than one strategy in learning vocabulary. The dominant Vocabulary Learning Strategy (VLS) used by male students was metacognitive strategies (63%), and the least is memory strategies (47%). Meanwhile, the dominant Vocabulary Learning Strategies (VLS) used by female students were metacognitive strategies (72%), and the least determination strategies (54%). This finding also revealed no statistically significant difference in male and female students’ use of the five categories and individual VLSs.